Compounds isolated at the Department of Biogenesis of Natural Substances, Institute of Microbiology, Czechoslovak Academy of Sciences, in 1954-1983 - Podojil, M; Cudlín, J; Vanĕk, Z (Folia microbiologica, 1984)
Substances studied at this department in 1954-1983 are reviewed; a total of 226 compounds are characterized in a tabular form. They include natural compounds as well as those prepared by biotransformation, by semisynthetic and synthetic methods.
Keywords: mikrobiologie; Microbiology; Organic Chemistry Phenomena; Anti-Bacterial Agents; antibakteriální látky; Chemistry, Organic; pojmy organické chemie; organická chemie